Landscapes of Mars A Visual Tour - Vogt, Gregory L. (Springer New York : Imprint: Springer, 2008)
Landscapes of Mars is essentially a picture book that provides a visual tour of Mars. All the major regions and topographical features will be shown and supplemented with chapter introductions and extended captions. In a way, think of it as a visual tourist guide. Other topics covered are Martian uplands on the order of the elevation of Mt. Everest, Giant volcanoes and a rift system, the Grand Canyon of Mars, craters and the absence of craters over large regions (erosion), and wind shadows around craters, sand dunes, and dust devils. The book includes discussions on the search for water (braided channels, seepage, sedimentary layering, etc.) as well as on the Viking mission search for life, Mars meteorite fossil bacteria controversy, and planetary protection in future missions. The book concludes with an exciting gallery of the best 3D images of Mars making the book a perfect tool for understanding Mars and its place in the solar system.